The proangiogenic effects of extracellular vesicles secreted by dental pulp stem cells derived from periodontally compromised teeth - Huan Zhou; Xuan Li; Yuan Yin; Xiao-Tao He; Ying An; Bei-Min Tian; Yong-Long Hong; Li-An Wu; Fa-Ming Chen (Stem Cell Research & Therapy, 2020)
Abstract Background Although dental pulp stem cells (DPSCs) isolated from periodontally compromised teeth (P-DPSCs) have been demonstrated to retain pluripotency and regenerative potential, their use as therapeutics remains largely unexplored. In this study, we investigated the proangiogenic effects of extracellular vesicles (EVs) secreted by P-DPSCs using in vitro and in vivo testing models. Methods Patient-matched DPSCs derived from periodontally healthy teeth (H-DPSCs) were used as the control for P-DPSCs. Conditioned media (CMs) derived from H-DPSCs and P-DPSCs (H-CM and P-CM), CMs derived from both cell types pretreated with the EV secretion blocker GW4869 (H-GW and P-GW), and EVs secreted by H-DPSCs and P-DPSCs (H-EVs and P-EVs) were prepared to test their proangiogenic effects on endothelial cells (ECs). Cell proliferation, migration, and tube formation were assessed using the Cell Counting Kit-8 (CCK-8), transwell/scratch wound healing, and Matrigel assays, respectively. Specifically, quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) and western blot analysis were used to examine the expression levels of angiogenesis-related genes/proteins in ECs in response to EV-based incubation. Finally, a full-thickness skin defect model was applied to test the effects of EVs on wound healing and new vessel formation. Results Both H-CM and P-CM promoted EC angiogenesis, but the proangiogenic effects were compromised when ECs were incubated in H-GW and P-GW, wherein the EV secretion was blocked by pretreatment with GW4869. In EV-based incubations, although both H-EVs and P-EVs were found to enhance the angiogenesis-related activities of ECs, P-EVs exerted a more robust potential to stimulate EC proliferation, migration, and tube formation. In addition, P-EVs led to higher expression levels of angiogenesis-related genes/proteins in ECs than H-EVs. Similarly, both P-EVs and H-EVs were found to accelerate wound healing and promote vascularization across skin defects in mice, but wounds treated with P-EVs resulted in a quicker healing outcome and enhanced new vessel formation. Conclusions The findings of the present study provide additional evidence that P-DPSCs derived from periodontally diseased teeth represent a potential source of cells for research and therapeutic use. Particularly, the proangiogenic effects of P-EVs suggest that P-DPSCs may be used to promote new vessel formation in cellular therapy and regenerative medicine.